Physical layer security of reconfigurable intelligent surface empowered wireless network with cooperative jammer - Kehinde Oluwasesan Odeyemi; Pius Adewale Owolawi; Olakanmi Oladayo Olufemi (Bulletin of Electrical Engineering and Informatics, 2022)
This paper evaluates the physical layer security performance of a reconfigurable intelligent surface (RIS) enabled wireless network in the presence of a passive eavesdropper. To secure the information transmission, a cooperative jammer is proposed to generate interference signal that degrade the performance of the eavesdropper. The source-to-RIS and RIS-to-destination links are subjected to Rician and Rayliegh fading distributions with phase errors, respectively, while other transmission links in the network follow the Nakagami-m fading distributions. The system phase error of the RIS is estimated by the von Mises distribution. To quantify the secrecy performance of the concerned system, the exact closed-form expressions in terms of connection outage probability (COP), security outage probability (SOP), and secrecy throughput (ST) are derived. In addition, the asymptotic expression of the system COP is obtained at high signal-to-noise ratio (SNR), providing more insight about the system performance. The accuracy of the derived expression is justified by Monte Carlo simulation. Also, the results clarify the analysis of the security performance, taking into account the impact of system and channel parameters on the system.